Development of Literary Competence Through the Reading of Short Stories as a Strategy to Promote Creative Writing - Echavarría, Karoll Juliana Henao; Alvarado, Sara Isabel Vásquez; Guevara, Jhenifer Mailec Rincón; Thomas, Rina Paola Royero; Villa, Yesica María Gil; Atencio, Carol Morela Miranda (Journal of Posthumanism, 2025)
This scientific article aims to promote the development of literary competencies in secondary and high school students, with greater emphasis on textual production, given its long-term significance for the situational factors that arise throughout a student’s life. These skills are essential for encouraging the formation of learners who feel interest and motivation for what they read and, in turn, are attracted to creative writing supported by short stories. It is important to highlight that strengthening these skills enables students to develop their own concepts as well as critical thinking and personal identity. This article was developed under a qualitative, documentary research approach, addressing the topic of literature teaching by considering previous research and analyses conducted in various documents, projects, and scientific articles related to this theme. Likewise, within the sources consulted, a clear distinction is made regarding the research line categorized within the field of pedagogies and/or didactics, oriented toward the sub-line of pedagogical models. Regarding the results obtained by different authors, the overall objective, the appropriate development of literary competencies, was achieved, as evidenced by the assessments conducted. Moreover, the strengthening of the skills encompassed by literary competence, such as comprehension, interpretation, analysis, and evaluation of texts, was accomplished.